The Evolution of Sports Medicine: From Rehabilitation to Performance Enhancement - Ahmad Bin Sulaiman (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sports medicine has developed into a field with a wide range of applications as a result of its shift from a reactive approach focused on injury recovery to a proactive one focused on performance development. This paradigm change affects general sports and fitness, healthcare, research, everyday wellness, and elite athlete management. Precise injury avoidance techniques, individualized training plans based on data-driven insights, and the use of precision medicine concepts are advantageous for elite athletes. Once only available to the wealthy and powerful, genetic discoveries are now influencing general healthcare and bringing in the age of personalized medicine. Sports medicine's influence on the general public is shown in the rise of wearable technology, which provides resources for tracking and improving fitness levels. For measuring the research used smart PLS software and generate results included descriptive statistic, correlation coefficient and smart PLS Algorithm model between them. Energy optimization, weight control, and general health methods are informed by nutritional advice gleaned from the practices of professional athletes. Athlete-specific rehabilitation procedures are easily incorporated into general physiotherapy settings, providing advantages to those outside sports. Diagnostic innovations that were first introduced in sports medicine, such as advanced imaging methods, are now essential to diagnosing and following up many medical disorders. Sports medicine concepts like motion analysis and biomechanics spur innovation in injury prevention and ergonomic design. This research illustrates the significant influence that sports medicine has had on a variety of fields, encapsulating its revolutionary journey. The overall research founded direct and significant link between them. The transition from rehabilitation to performance enhancement represents a dynamic and far-reaching change in our understanding of health, well-being, and human potential. It has the potential to drastically alter the management of top athletes as well as have an impact on healthcare, research, and daily wellness.